Allosteric activation of vinculin by Talin [data] - Gräter, Frauke; Franz, Florian; Winograd-Katz, Sabina; Tapia-Rojo, Rafael; Boujemaa-Paterski, Rajaa; Li, Wenhong; Unger, Tamar; Albeck, Shira; Aponte-Santamaria, Camilo; Garcia-Manyes, Sergi; Medalia, Ohad; Geiger, Benjamin (Universität, 2023)
The talin-vinculin axis is a key mechanosensing component of cellular focal adhesions. How talin and vinculin respond to forces and regulate one another remains unclear. By combining single molecule magnetic tweezer experiments, Molecular Dynamics simulations, actin bundling assays, and adhesion assembly experiments in live cells, we here discover a two-ways allosteric network within vinculin as a regulator of the talin-vinculin interaction. We directly observe a maturation process of vinculin upon talin binding which reinforces the binding to talin at a rate of 0.03 s−1. This allosteric transition can compete with force-induced dissociation of vinculin from talin only at 7-10 pN. Mimicking the allosteric activation by mutation yields a vinculin molecule that bundles actin and localizes to focal adhesions in a force-independent manner. Hence, the allosteric switch confines talin-vinculin interactions and focal adhesion build-up to intermediate force levels. The ‘allosteric vinculin mutant’ is a valuable molecular tool to further dissect the mechanical and biochemical signalling circuits at focal adhesions and elsewhere.